2011
DOI: 10.15666/aeer/0901_043072
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on Lepidoptera Species and Communities

Abstract: Abstract. In this review, the impacts of climate change on Lepidoptera species and communities are summarized, regarding already registered changes in case of individual species and assemblies, and possible future effects. These include changes in abundance, distribution ranges (altitude above sea level, geographical distribution), phenology (earlier or later flying, number of generations per year). The paper also contains a short description of the observed impacts of single factors and conditions (temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 164 publications
1
34
0
6
Order By: Relevance
“…In addition to causing local and regional extinctions, climate change can alter the size and location of the range and patterns of abundance and phenology of species [38]. Many lepidopterans, including Arctiinae species [65], are agricultural pests and changes in range, abundance and phenology of these species may increase the rate of invasion and increase the damage intensity they can cause [66], [67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to causing local and regional extinctions, climate change can alter the size and location of the range and patterns of abundance and phenology of species [38]. Many lepidopterans, including Arctiinae species [65], are agricultural pests and changes in range, abundance and phenology of these species may increase the rate of invasion and increase the damage intensity they can cause [66], [67].…”
Section: Discussionmentioning
confidence: 99%
“…In animals, an increasing number of studies have shown changes in species distributions related to warming and drought (Guo et al ., ; Lenoir et al ., ; Kocsis & Hufnagel, ). Because of their higher mobility, animals have a greater capacity than plants to escape unfavorable climatic conditions.…”
Section: Responses Of Populationsmentioning
confidence: 99%
“…These changes can increase their population in the recent inhabited areas and by moderating the climate in the temperate areas of Europe can facilitate the migration of these arthropod vectors to North (De la Roque et al, 2008).Higher temperatures can induce earlier flight of adult insects, eg. Lepidoptera species (Kocsis and Hufnagel, 2011).The human factors, travelling, livestock are also important determinants of the abundance (Ready, 2010). Rioux et al (1985) found that the raising of temperature significantly increased the overall proportion of infected sandflies.Heat, humidity, and sufficient organic matter are the main effectors of the larval development of sand fly species (Naucke, 2002;Lindgren and Naucke, 2006), while the increasing CO 2 levels are usually unfavourably affecting the development of the insect larvae (Kocsis and Hufnagel, 2011).The differences in the environmental requirements between Phlebotomus species are noticeable in their different habitats: in France P. ariasi mostly live in the wet and mild climate of mountain forests, while P. perniciosus occupy the warm and drier Mediterranean coastal plains (Chamailléet al, 2010).Leishmaniasis is an emerging disease in Europe and one of the first signs of the establishment in a new area of leishmaniasis is that the parasite makes new autochthonous foci in the dog populations (Köhler et …”
Section: Introductionmentioning
confidence: 99%